A New Species of the Genus Ormyrus (Hymenoptera, Chalcidoidea, Ormyridae) from Yemen - Zerova, M.D.; Seryogina, L.Ya.; van Harten, A. (Інститут зоології ім. І.І. Шмальгаузена НАН України, 2006)
Ormyrus bicolor Zeriva, sp. n. from Yemen is described. The new species belongs to diffinis group of species (female gaster without dorsal median keel).